One-step preparation of alpha-chlorostyrenes - Borate, Hanumant B.; Galkwad, Abaji G.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Kalal, Kamalakar M. (Tetrahedron Letters, 2007)
alpha-Chlorostyrenes were prepared via a one-step method involving Friedel-Crafts reaction of various aromatic substrates with acid chlorides in the presence of a heterogeneous Si-Fe catalyst. (c) 2007 Elsevier Ltd. All rights reserved.